Effect of NaCl Replacement by other Salts on the Quality of Bísaro Pork Sausages (PGI Chouriça de Vinhais) - Alfredo Teixeira; Rubén Domínguez; Iasmin Ferreira; Etelvina Pereira; Leticia Estevinho; Sandra Rodrigues; José M. Lorenzo (Foods, 2021)
Concerned about the trend to reduce salt consumption, the meat industry has been increasing the strategies to produce and commercialize products where the reduction or even the replacement of NaCl is an important goal. The aim of this study was to test the effect of partial NaCl replacement by KCl and Sub4Salt® on the quality of pork sausages. Three different formulations (NaCl + KCl, NaCl + Sub4Salt®, and KCl + Sub4Salt®) were considered and compared to the control (2% NaCl). Physicochemical properties, chemical composition, and microbiological and sensory characteristics were evaluated. The replacement of NaCl did not affect pH, water activity (aw) or its chemical composition after eight or 16 days ripening time, while a significant sodium reduction was achieved. The oxidation index expressed in TBARS was also not affected by the NaCl substitution and varied between 0.01 to 0.04 of malonaldehyde (MDA) per kg of sample. Similarly, the NaCl replacement did not change the microbiological quality of the sausages, and the production of healthier meat sausages had also no significant effect on their sensory characteristics. Therefore, according to the results obtained, it is viable and a good strategy for the meat industry to produce “reduced sodium content” sausages without affecting their traditional quality.